Profil Resiliensi Akademik Berdasarkan Jenis Kelamin pada Siswa Sekolah Menengah Kejuruan - Setyani Alfinuha (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: Vocational High School students face a dual burden of academic demands and practical skills oriented toward the world of work. Such pressures often lead to academic stress, anxiety, and decreased learning motivation. Academic resilience becomes an important aspect that enables students to endure, adapt, and recover from learning challenges. Objective: The aim of the study is determining the level of academic resilience of students at SMK X and to test differences in academic resilience based on gender. Academic resilience is the ability of students to survive, adapt, and bounce back from pressure or obstacles in the context of learning. Method: This study uses a descriptive quantitative approach and a different test with an instrument in the form of an academic resilience scale. The sampling technique used is a population sample where the entire population becomes participants in this study. The number of research participants is 371 SMK X students. Result: The results of the analysis show that most students have a relatively low level of academic resilience. This indicates that many students do not have adequate resilience in facing academic challenges in the school environment. In addition, the difference test shows that there is no significant difference between the academic resilience of male and female students. This finding indicates that gender factors do not significantly affect the level of academic resilience. Conclusion: Based on these results, it is recommended that schools develop psychological programs or interventions that can improve students' academic resilience without distinguishing between genders.